Electrochemical Study of Prussian White Cathodes with Glymes – Pathway to Graphite‐Based Sodium‐Ion Battery Full Cells. Issue 7 (1st April 2022) - Gourang Patnaik, Sai; Escher, Ines; Ferrero, Guillermo A.; Adelhelm, Philipp
Abstract: Prussian white (PW) cathodes exhibit extremely fast rate kinetics for sodium ion (Na + ) insertion/de‐insertion at relatively high potentials. However, one of the major bottlenecks is to pair them with appropriate anode materials having similar rate kinetics. Herein, the combination of graphite anodes and several glyme‐based electrolytes as appropriate building blocks for PW cathodes to achieve high power density without compromising on energy density is reported. Low defect, Na‐rich PW is synthesized, and its electrochemical behavior is studied with conventional carbonate‐based electrolytes as well as with diglyme (2G), tetraglyme (4G) and a 1 : 1 mixture of 2G and 4G. The stability of the electrolytes is also monitored via in situ (operando) pressure cell measurements. Graphite |  electrolyte |  PW cells are then studied in both two and three electrode configurations. It was found that glymes are compatible with the graphite/PW electrode pair and the resulting cells exhibit very good cyclability and rate capability. Abstract : Glyme electrolyte boosts : Graphite as fast charging anode in combination with glyme‐based electrolytes is coupled with Prussian white (PW) cathodes to achieve cells with high power characteristics without compromising on energy density. Both diglyme and tetraglyme exhibit excellent cycling stability and rate capacity retention in graphite |  (electrolyte) |  PW cells. Glymes also exhibit enhanced electrochemical properties as compared to conventional carbonate‐based electrolytes with PW cathodes.